Reconstruction of maxillary ridge atrophy caused by dentoalveolar trauma, using autogenous block bone graft harvested from chin: a case report - Souza, Francisley Avila [UNESP]; Bassi, Ana Paula Farnezi [UNESP]; Aranega, Alessandra Marcondes [UNESP]; Ponzoni, Daniela [UNESP]; Leonardi, Gabriela Bufulin [UNESP]; Boos, Fernanda Brasil Daura Jorge [UNESP]; Luvizuto, Eloá Rodrigues [UNESP]; Nímia, Heloísa Helena; Garcia Júnior, Idelmo Rangel [UNESP] (My University, 2014)
Background Dentoalveolar trauma, especially when involving front teeth, negatively affect the patient’s life; in particular, tooth avulsion is a complex injury that affects multiple tissues, and no treatment option offers stable long-term outcomes. The aim of this study was to report a case of reconstruction of atrophic anterior alveolar ridge after tooth loss, performed with autograft harvested from the chin, and subsequent prosthetic rehabilitation with the use of an osseointegrated implant. Case report A 23-years-old Caucasian girl, presented an atrophic alveolar bone in the area of tooth 11, as a result of tooth resorption 10 years after a tooth reimplantation procedure. Reconstruction was performed with autogenous bone harvested from the chin. After 6-months healing period to allow autograft incorporation, a dental implant was inserted. After further 6- months, a screw-retained implant supported metal-ceramic prosthesis was fabricated. Results The prosthetic rehabilitation was successful, and after a follow-up period of 5 years, the achieved result was stable.Conclusion It can be concluded that the autogenous bone graft harvested from the chin, is a safe and effective option for alveolar ridge defects reconstruction, allowing a subsequent placement of a dental implant supporting a prosthetic restoration.